2012
DOI: 10.1016/j.pain.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Is there a potential role for attention bias modification in pain patients? Results of 2 randomised, controlled trials

Abstract: Potential applications of attention bias modification (ABM) for acute and chronic pain patients are investigated. In study 1, 54 acute back pain patients (46 of whom completed the study) were recruited at their initial physiotherapy session and randomised to receive 1 session of ABM or placebo. Patients were followed up 3 months later. Participants who were randomised to receive ABM reported less average (P=0.001) and current pain (P=0.008) and experienced pain for fewer days (P=0.01) than those who received p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
121
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 43 publications
8
121
1
2
Order By: Relevance
“…Collectively, such findings suggest that AB toward pain may contribute to greater pain/difficulty appraisals of everyday physical activity, and may ultimately contribute to greater disability. Accordingly, these findings further attest to the critical role of modifying attention to pain within clinical interventions or its underlying cognitions that fuel AB for pain [34,47].…”
Section: Discussionmentioning
confidence: 69%
“…Collectively, such findings suggest that AB toward pain may contribute to greater pain/difficulty appraisals of everyday physical activity, and may ultimately contribute to greater disability. Accordingly, these findings further attest to the critical role of modifying attention to pain within clinical interventions or its underlying cognitions that fuel AB for pain [34,47].…”
Section: Discussionmentioning
confidence: 69%
“…Several treatment options have been proposed. Recent findings suggest that attentional bias may be modified in such way that attention is directed away from fear-related information (e.g., [47]) and pain-related information (e.g., [33], but see [48]). Other treatment options that have been proposed are interventions that target the fear system and the threat value of pain as this has been argued to fuel attentional bias towards pain-related information [53,59].…”
Section: Discussionmentioning
confidence: 99%
“…Some consider such biases as etiopathological factors in the development, maintenance or exacerbation of pain problems [53,54]. In line with this view are the findings of an experimental study with healthy volunteers performing a cold-pressor task which showed that attentional retraining may affect peoples' pain threshold as well as their pain experience [37], indicating a causal influence of attentional bias towards pain-related information on pain outcomes.…”
mentioning
confidence: 85%